Bidirectional Trafficking of Prostaglandin E(2) Receptors Involved in Long-Term Potentiation in Visual Cortex - Akaneya, Yukio (J Neurosci, 2006)
Although prostaglandin E(2) (PGE(2)) has a broad spectrum of biological activities that have been confirmed by previous studies, the roles of PGE(2) in synaptic plasticity such as long-term potentiation (LTP) in the CNS have yet to be characterized in detail. The present results of electrophysiological and biochemical studies indicated that PGE(2) is actually produced in acute visual cortex slices in response to theta-bust stimulation (TBS) and is involved postsynaptically in TBS-induced LTP. RNA interference (RNAi) for PGE(2) receptor subtypes EP2 and EP3, which are known to upregulate and downregulate the level of cAMP, respectively, induced significant decreases and increases of LTP, respectively. Moreover, analysis of the localization of receptor subtypes at the membrane surface or cytosol showed that stimuli such as TBS regulate the trafficking of EP2 and EP3 between the membrane and cytosol of the postsynapses, rising up to and leaving the membrane, respectively, resulting in increased and decreased expression of EP2 and EP3 at the membrane, respectively. Increased activation of EP2 and decreased activation of EP3 by PGE(2) synergistically induce an increase in cAMP level, which may induce LTP. This causes activation of CREB (cAMP response element-binding protein) in the postsynaptic cells, which may be involved in the maintenance of LTP. These observations indicate that in TBS-induced LTP of the visual cortex, PGE(2) is released from the postsynaptic cells and then activates PGE(2) receptors at the postsynaptic membranes, which is regulated by trafficking of the differential PGE(2) receptor subtypes in an activity-dependent bidirectional manner.